TELEVISION AND WOMEN POLITICIAN (A Study About Representation, Women Appraisal and the Idea of Women Representation in Parliament Legislative Election 2009 on Television) - Widodo Muktiyo (The Indonesian Journal of Communication Studies, 2014)
Television plays an important role in shaping social cognition including in political domain. Television can construct social reality in line to its own interest that was playing for women politician to get good impression in political contestation for parliament election 2009. Correlation between television as one of mass media and woman politician was an important thing to describe a multifaceted of coordination and joint action to pursue a properly position for woman politician for parliament 2009. For these intentions, this research was done and executed in Gajahan, Pasar Kliwon Surakarta. Media technique and analysis were implemented here to reveal media tendencies for women politician in legislative election 2009. The results showed that television was still rarely describing women politician properly. Television just aired a few for women politician except celebrities that involve the contestation.